Building systems for interior designers - Binggeli, Corky (Wiley, 2016)
"The ultimate interior designer's guide to building systems and safety Building Systems for Interior Designers, Third Edition is the single-source technical reference that every designer needs, and an ideal solution for NCIDQ exam preparation. Now in its third edition, this invaluable guide has been updated to better address the special concerns of the interior designer within the context of the entire design team. New coverage includes the latest information on sustainable design and energy conservation, expanded coverage of security and building control systems, and a new and expanded art program with over 250 new illustrations. Covering systems from HVAC to water to waste to lighting, this book explains technical building systems and engineering issues in a clear and accessible way to help interior designers communicate more effectively with architects, engineers, and contractors. Professional interior design is about much more than aesthetics and decorating, and technical knowledge is critical. Before the space is planned, the designer must consider the mechanical and electrical equipment, structural system, and building components, and how they impact the space. This book shows you how to evaluate these complex factors, and how each affects your work throughout the building. Consider how site conditions and structural systems affect interior design Design functionally for human health and safety Factor water, electrical, and thermal systems into your design plans Examine the ways in which lighting and acoustics affect the space The comfort, safety, and ultimate success of a project depend upon your knowledge of building system and your coordination with architects and engineers. Building Systems for Interior Designers, Third Edition provides the comprehensive yet focused information you need to excel at what you do best"- Resumé vydavatele
Keywords: budovy; technická zařízení budov; projektování staveb; buildings; technological equipment of buildings; buildings design; příručky; handbooks and manuals